Corporate tax aggressiveness: evidence unresolved agency problem captured by theory agency type 3 - Bani Alkausar; Yanuar Nugroho; Alfiyatul Qomariyah; Ari Prasetyo (Cogent Business & Management, 2023)
This study examines corporate tax aggressiveness captured by agency problem type 3. The results show that there are negative relations between corporate governance and tax aggressiveness. The findings provide evidence of agency conflicts between companies and tax authorities. A corporate governance mechanism can improve the quality of corporate financial reporting. The result also illustrates how corporate governance affects the actions of corporate tax aggressiveness at various levels by using regression quantile analysis. It is believed that corporate companies with high levels of aggressiveness will make the mechanism of corporate governance in the company to be more effective.
Keywords: 650; agency problem; cash effective tax rate; Corporate governance; effective tax rate; financial reporting; tax aggressiveness; taxation